Measuring Self-Regulation of Distance Learners: A Comparative Study of Science and Arts Students - Farkhunda Rasheed Choudhary (International Islamic University Islamabad, 2020)
In distance learning, students’ self-regulation and autonomy has vital place. Learner’s selfregulation is a major predictor of the academic success of distance learner. The high rate of selfregulation increases the quality of distance education. Therefore, it is important to explore that how much self-regulated the distance learners are in a distance education mode. This study aimed at exploring the self-regulation strategies of science and arts students studying in a distance learning university. The present study was descriptive in nature and survey was used for it. A sample of forty students was selected through purposive sampling. Learners’ self-regulation was measured through research tool, having six constructs such as planning, monitoring, effort made by the distance learners to accomplish the course, self-efficacy, help-seeking situations, time and environment management situations. The data was collected through online questionnaire. It was found that distance learning science students were more self-regulated than arts students. Overall science students scored significantly higher grades than that of arts students. It is concluded that the science students are more self  regulated due to self monitoring for their studies, more goal setting and more group interdependence. Goal setting and group interdependence can be considered as contributor for high GPA of distance learners. For science students, group interdependence is a good predictor of more GPA, however, for arts students, future orientation can be a predictor of good GPA. It is recommended that more interaction must be increased between instructor and arts students so that they can be more self-regulated about their studies.